Food, agri-culture and tourism linking local gastronomy and rural tourism : interdisciplinary perspectives - Sidali, Katia Laura; Spiller, Achim; Schulze, Birgit (Springer Berlin Heidelberg, 2011)
This book will be a valuable source of information for those concerned with rural and farm tourism, sustainable tourism and the marketing of local gastronomy. It presents cases with an international and interdisciplinary approach in order to provide ideas for strategic perspectives in tourism studies. Furthermore, for the first time the complex fields of rural and food tourism are examined from an international (Italy and Germany) viewpoint. This book explores ways in which gastronomical heritage (i.e., regional food, organic food) can be incorporated in rural tourism (above all farm tourism) and development policies as well as in new avenues of research (e.g., sensory marketing, online marketing) in order to enhance sustainable practices both in the tourism and in the agri-food sector. Overall, the book presents an overview of benchmark practices for professionals (associations of rural tourism, farmers, etc.), while offering scholars a well-founded source to refer to in order to gain up-to-date insights into the state of the art of studies on rural and food touris